Zmiany strukturalno-czynnosciowe serca u sportowców kadry narodowej judo - Wysocki, K.; Multan, A.; Laskowski, R.; Maslowski, J. (Sport wyczynowy, 2002)
10 female and 13 male judo competitors' health condition has been examined by means of echographic heart tests (AoD, Dd, IVST, LVPWT), tests on some of the parameters of the circulatory system (HR,RR, stroke volume and cardiac output) but also VO2max (by means of direct method), anaerobic capacity and the amount of performed work (by means of Bar-Or method). The ventricular septal overgrowth has been diagnosed within over the half of the tested individuals and to 23% of them the thickening of the posterior wall of the left ventricle has been reported. It suggests influence of the intensified pressure action of heart which presumably results from the character of the workload of the mentioned sport discipline, which is abundant in periodical raise in endocardiac pressure (Walsalw's rule). The case concerns such situations as holding the competitor, stifling and applying the catches in the course of fight. All the examined athletes have shown high parameters of achieving anaerobic capacity and the amount of the performed work in oxygen deficit conditions. On the other hand, the visualization of the overgrowth in diastolic size of the left ventricle, which may show the increased capacity (diastolic) load of heart (Sterling's rule), has been reported within 32% of females and 10% of males. It has been accompanied by a proper oxygenic capacity (VO2max). Observed low values of the frequency of cardiac contractions and arterial blood pressure in resting conditions may prove that the circulatory system got well adapted to physical exercises and restitution efficiency. Moreover, slightly increased values of stroke volume and cardiac output, found within some of the athletes (20%) may appear as a result of the intensified vegetative tension of neural system, and also the after-training factors. The analysis of the blood flow in cardiac cavities and the work of cardiac valves has shown the existence of retrogressive blood flow through the valves, however without the raise in the pressure of cardiac cavities, within 6% of the competitors. The existence of the degenerative changes in leaflets of the mitral valve has been found in one case only, which proves the usefulness of echographic tests - especially dynamic tests (stress echo) in terms of medical care programme for achievements athletes.